“I Embrace my ashes”: North Korean migrants learning about entrepreneurship from failure - Jinhee Choi; Esther Prins (Adult Education Research Conference, 2020)
Migrants’ workplace experiences in their host society shape their social adjustment, yet how migrants learn from failures is under-investigated. This study examined how North Korean migrants in South Korea sought to learn from failures in their workplaces and everyday life. The paper draws on nine months of ethnographic research in South Korean social enterprises (restaurants, cafes) that employ North Korean migrants. Data sources include informal conversations and loosely structured interviews with five purposefully selected women who started, or planned to start, their own enterprise. The findings revealed that migrants experienced failure in five inter-related spheres: financial, relational, physical, psychological, and professional. Participants developed perspectives to understand failure as an integral part of learning in a new society and adopting unfamiliar role expectations and responsibilities. They also applied knowledge from their failures to change their approach to their career and strengthen their personal and business capacity to obtain a legitimate social position. Paradoxically, failures that were beyond their control, such as legal problems, created opportunities to receive practical support from, and increase trust in, South Koreans. These findings contribute to adult education scholarship on migrants’ situated learning in their host societies and challenge the discourse that portrays North Korean defectors as deficient.
Keywords: Entrepreneurship; Migration studies; North Korean defectors; North Korean migrants; Workplace learning